Controlling Water Quality of a Firm's Hydropower - Al-Matar, Najeeb; Tadj, Lotfi (International Journal of Global Operations Research, 2023)
The problem considered in this paper concerns a manufacturing firm located at a lake. The firm uses the lake's water in its production process. However, the production process affects the quality of the water. The manufacturing firm will only survive if the natural resource it uses, namely water in this case, remains available for the long term. Sustainability can be achieved through green manufacturing practices. The problem is dynamic, and optimal control theory, namely model predictive control, is used to determine the optimal production rate and the optimal rate of expenditure for pollution control. A numerical example illustrates the results obtained.Â